Revealed Preference Tests of the Cournot Model - Carvajal, Andrés; Deb, Rahul; Fenske, James; Quah, John K.-H. (Econometrica, 2013)
The aim of this paper is to develop revealed preference tests for Cournot equilibrium. The tests are akin to the widely used revealed preference tests for consumption, but have to take into account the presence of strategic interaction in a game-theoretic setting. The tests take the form of linear programs, the solutions to which also allow us to recover cost information on the firms. To check that these nonparametric tests are sufficiently discriminating to reject real data, we apply them to the market for crude oil.